Principles For Developing Effective Project Schedules Under Extreme Climate Conditions - Valentin George Cretu (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
The article provides principles for creating efficient project schedules in extreme climatic conditions. The rationale for the relevance of the work is essentially defined, considering recent trends regarding the increasing frequency and magnitude of weather-related catastrophes. The purpose here is to develop a methodology for adaptive planning based on quantitative diagnostics regarding climate, probabilistic windows related to favorable conditions, and the dynamic redistribution of tasks. It will be new in that non-stationary extremes will be integrated within an analysis approach to evaluate changes in parameters regarding climate distributions; climate windows shall be calculated based on multi-year meteorological data and NOW-cast forecasts; adaptive buffers shall be applied within the critical chain by APD rule and modular decomposition of tasks; the digital twin will function to perform operational revision of priorities; finally parametric insurance as well as climate clauses shall be included in contracts. The main conclusions affirm that the application of the above-stated rules allows up to 28% acceleration of the calendar with budget maintenance, reduces downtime uncertainty by 15%, and keeps schedule shifts within 5% of the planned date for up to three years. This paper is likely to find its best audience among project managers, planners, and risk management specialists working in the building construction, infrastructure, and maritime sectors.